2021
DOI: 10.1016/j.envsoft.2021.105167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two sets of Monte Carlo estimators of Sobol’ indices

Abstract: This study compares the performances of two sampling-based strategies for the simultaneous estimation of the first-and total-order variance-based sensitivity indices (a.k.a. Sobol' indices). The first strategy corresponds to the current approach employed by practitioners and recommended in the literature. The second one was only recently introduced by the first and last authors of the present article. Both strategies rely on different estimators of first-and total-order Sobol' indices. The asymptotic normal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…In order to identify the input factors that exert the largest influence on the ranking, we conducted a variance-based SA. We estimated Sobol' first-and total effect sensitivity indices using the state of the art Azzini et al (2020) estimator. The SA revealed that a potential measurement error, the omission of individual indicators, different conceptual optima used for selected EQx indicators, as well as the aggregation method at the sub-index level have negligible effects on the country ranking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to identify the input factors that exert the largest influence on the ranking, we conducted a variance-based SA. We estimated Sobol' first-and total effect sensitivity indices using the state of the art Azzini et al (2020) estimator. The SA revealed that a potential measurement error, the omission of individual indicators, different conceptual optima used for selected EQx indicators, as well as the aggregation method at the sub-index level have negligible effects on the country ranking.…”
Section: Discussionmentioning
confidence: 99%
“…They empirically compare eight MC-based estimators for the total-sensitivity index. The estimator developed by Azzini et al (2020) is one of the best performing, both when the goal is to rank input factors according to their contribution to model output variance (factor prioritisation setting), as well as when the aim is to approximate the "true" indices (factor fixing setting) (p.12). Thus, the Azzini estimator is recommended by Puy et al (2021b, p. 19), since it is both efficient and robust to a wide range of practical situations.…”
Section: Estimation Of First-and Total-order Sobol' Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The model f runs row-wise in each matrix, and we use the model output y to compute the coefficient of variance and the sensitivity indices. We compute S i and T i with the Azzini estimators ( 66 )Si=2truetrue∑v=1Nfalse(ffalse(BAfalse(ifalse)false)vffalse(bold-italicBfalse)vfalse)false(ffalse(bold-italicAfalse)vffalse(ABfalse(ifalse)false)vfalse)truetrue∑v=1Nfalse[false(ffalse(bold-italicAfalse)vffalse(bold-italicBfalse)vfalse)2+false(ffalse(BAfalse(ifalse)false)vffalse(ABfalse(ifalse)false)vfalse)2false]Ti=truetrue∑v=1Nfalse[ffalse(bold-italicBfalse)vffalse(BAfalse(ifalse)f...…”
Section: Methodsunclassified